The Space-Charge Effect on Theoretical Design of the Electron Gun Operated under Finite Magnification Condition - Hussein, B.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A computer theoretical s1udy has been carried out in field of opto - clcctroniccs, to design  an electron  gun using the space charge effect.The   distribution  of   axial  potential    upon   the  two   -electrodeimmersion  lens  of  (L=l4mm)  has been  carried   out   using   Poisons equation and the  tinite  clement  method;  knowing  the first 11nd second derivation  of  the    axial   potential   and  the  solution   of  paraxial   ray equation, the  optical   properties of  the  focal   length. (Spherical and Chromatic aberration Coefficients) been founds.An   acceptable  values   for   Splerical   and   Chromatic  aberrationCoefficients aberration coefficients abtained  when a current  of (I= I o-4• A) applied with a been ofunifom1 cross-sectional area S=lmm 2.